On p-adic cubic generalized logistic dynamical system - Mukhamedov, Farrukh; Wan Rozali, Wan Nur Fairuz Alwani (IOP Publishing Ltd, 2013)
Applications of p-adic numbers mathematical physics, quantum mechanics stimulated increasing interest in the study of p-adic dynamical system. One of the interesting investigations is p-adic logistics map. In this paper, we consider a new generalization, namely we study a dynamical system of the form fa(x) = ax(1−x2). The paper is devoted to the investigation of a trajectory of the given system. We investigate the generalized logistic dynamical system with respect to parameter a and we restrict ourselves for the investigation of the case |a|p < 1. We study the existence of the ﬁxed points and their behavior. Moreover,wedescribetheirsizeofattractorsandSiegeldiscssincethestructureoftheorbitsofthesystem is related to the geometry of the p-adic Siegel discs.